PENGARUH PENERAPAN VALUE FOR MONEY DALAM PENGELOLAAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA KANTOR BPKD KABUPATEN BIREUEN) - Aulia, Jihan Risky; Fuadi, Raida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to see and analyze how Value for Money influences the financial management of the Bireuen district government. The population to be studied in this study are all employees at the BPKD office in Bireuen district and for sampling to be used is probability sampling which is a random sampling method. The data analysis method used is multiple linear regression with the help of using the SPSS Version 26 application. Based on the results of the research and discussion that has been carried out, the authors can conclude that Economy, Efficiency, and Effectiveness, simultaneously affect government financial management at the BPKD office in Bireuen Regency. The importance of increasing Value for Money (economy, efficiency, and effectiveness) in order to create quality local government financial management.